Implementasi Program Tahsin dalam Meningkatkan Kualitas Bacaan Al-Qur’an Santri di Yayasan Griya Fadhilah Al- Qur’an: Studi Qs. Al-Muzzammil: 4 (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
The tahsin Al-Qur’an program is designed to improve the ability to recite the Qur’an in accordance with the rules of tajwid and the principle of tartil. This study examines the implementation of the tahsin program in enhancing the quality of Qur’anic recitation among students at Yayasan Griya Fadhilah Al-Qur’an, with reference to Qur’an Surah Al-Muzammil verse 4 as a normative foundation. This research employs a qualitative approach with a case study design. Data were collected through observation of the learning process, interviews with instructors and program administrators, and analysis of program documents. The findings indicate that the tahsin program is implemented in a structured manner through training in makhārij al-ḥurūf, strengthening of ṣifāt al-ḥurūf, application of tajwid rules, and habituation of gradual and continuous Qur’anic recitation. The implementation of the program contributes to improved accuracy of pronunciation, fluency of recitation, and students’ awareness of the importance of reciting the Qur’an in accordance with Islamic teachings. Therefore, the tahsin program plays a significant role in improving the quality of Qur’anic recitation among students. Overall, this tahsin program not only improves the quality of Quran reading, but also deepens students' understanding of the values ​​contained in the Quran.